Phase separation of a master transcription factor targeted by a natural compound regulates fungal ergosterol homeostasis - Wang, Huiyuan; Wang, Yuhua; Wang, Jingrui; Wang, Mengcen; Yin, Yanni; Chen, Yun; Liu, Zunyong; Li, Gang; Ma, Zhonghua (Science China. Life sciences, 2025)
Although cellular sterol sensing and regulation of sterol biosynthesis are essential processes for eukaryotes, the mechanisms governing ergosterol homeostasis remain largely unknown in pathogenic fungi. In this study, we identify the transcription factor FfSR as a key regulator of sterol homeostasis in Fusarium fujikuroi , the causative agent of rice bakanae disease worldwide. Deletion of FfSR results in reduced ergosterol levels, increasing the susceptibility of F. fujikuroi to azole fungicides. Mechanistically, azole-induced ergosterol depletion promotes FfSR phase separation, which facilitates its binding to cis -elements at target promoters, subsequently activating the expression of ergosterol biosynthesis genes. Conversely, when ergosterol levels are high, ergosterol binds to FfSR, inhibiting its phase separation and transcriptional activation. Additionally, we identify a natural compound, natamycin, as a direct inhibitor of FfSR, suppressing its phase separation and transcriptional capability. These findings highlight a novel mechanism by which fungal pathogens regulate ergosterol homeostasis through transcription factor phase separation, indicating that small molecules targeting FfSR could serve as a synergist to enhance azole efficacy against pathogenic Fusarium .